A companion to African American history - Hornsby, Alton (Blackwell companions to American history., 2005)
A Companion to African American History is a collection of original and authoritative essays arranged thematically and topically, covering a wide range of subjects from the seventeenth century to the present day. From their origins in West Africa on the eve of slave trading, through slavery itself and its abolition in the turmoil of the Civil War, and then over the rest of the nineteenth century and into the twentieth, as they struggled for freedom, identity, and place, African Americans occupy a central role in their country's history. This volume surveys the scholarly literature in African American history and provides a guide to the research, analyses, and various interpretations and perspectives that historians have developed over the past fifty years. Each essay pays particular attention to geographical features as well as conceptual and methodological issues. In this volume, globalization, region, migration, gender, class, and social forces have been knitted into the broad cultural fabric of African American history.; With this Companion, readers now have a complete source to the most recent theories and explanations for the changing contours of African American life.